Energy Saving Analysis on Distribution Network with Incorporation of D-STATCOM Using Firefly Algorithm and Power Loss Index - Olabode, Olakunle Elijah; Ajewole, Titus Oluwasuji; Ariyo, Funso Kehinde (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2024)
This present work investigated the effects of reactive power compensation with the use of a Distribution Static Synchronous Compensator (D-STATCOM) on a practical distribution network. In the approach proposed, the network steady-state parameters were obtained with a backward forward sweep power flow technique, the possible sites for D-STATCOM were predetermined with power loss index while the firefly algorithm was employed for determining the optimal sizes and sites respectively. Three different levels of D-STATCOM penetrations were investigated and their effects on voltage profile enhancement, active power loss reduction, cost of energy savings, payback times, and cost of procurement were assessed. The best optimal sites and sizes obtained after several simulations for case I, case II, and case III are (6, 1000kVar); (12, 349.69kVar; 22, 867.29kVar) and (5, 1200kVar; 14, 424.34kVar; 21, 350kVar) respectively. Also, the percentage improvements at the bus with minimum voltage magnitude for cases I to III are 0.6, 0.78, and 0.79% while the accompanied active power loss reductions are 59.03, 70.57 and 91.78 %. From the economic perspective, the cost of procurement ($), annual energy savings ($), and the payback time (years) for the three cases examined are (5,303.5, 1,461.00, 3.63); (6,454.25, 1,746.66, 3.69); (10,471, 2, 271.58, 4.61) respectively. Also, results validation showed that the approach proposed outsmarts particle swarm optimization and network feeder reconfiguration. The outcome of this work findings application in performance enhancement of real-life distribution networks.